Percepções de professoras de creche sobre formação, saberes e reconhecimento profissional - Nonato, Giovana Regina (2023)
This qualitative research aimed to understand, through the perceptions of preschool eachers, the processes related to training, knowledge, and professional recognition.Starting from the following research question: What are the perceptions of preschoolteachers regarding their formative processes, teaching knowledge, and professionalrecognition? In this sense, a survey of research in the area on the topic was conductedinitially, followed by the application of questionnaires and interviews with 10 earlychildhood education teachers working with children aged 0 to 3 years old, at a CEMEIin the municipality of São Carlos-SP. As a backdrop for the analysis, authors from thetheoretical perspective of the epistemology of practice (Alarcão (1996); Freire (1996);Gauthier (2006); Goodson (2015); Nóvoa (1995); Pimenta (2000); Tardif (2012)); andfrom the field of early childhood education were used: Arce (2001); Assis (2007);Oliveira (2014); Onofre, Tomazzetti, and Martins (2017), among others. We believethat the results of the study contributed to strengthening the professionalizationmovement of teachers working at this level of education and to the importance of theprotagonism of their knowledge. The relevance of this study was also justified inpersonal relevance, contributing directly to teaching practice and the school unit of theresearch proponent; in political-pedagogical relevance, considering the possibility oflistening to teachers, pointing out the need for an effective policy of valorization andrecognition of these professionals; in academic relevance, for the perspective ofstrengthening the movement of teacher professionalization. The study showed thatinitial training courses were not sufficient for work in the field, as they did not addressthe specificities of early childhood education; it pointed out that the participants in theresearch are not socially and professionally valued; it reinforced the lack of theirparticipation in political decisions and, finally, it noted the absence of speech andlistening from various instances, promoting silence and the proletarianization of thecategory.